Active coping strategies and less pre-pandemic alcohol use relate to college student mental health during the COVID-19 pandemic - Akeman, Elisabeth; Cannon, Mallory J.; Kirlic, Namik; Cosgrove, Kelly T.; DeVille, Danielle C.; McDermott, Timothy J.; White, Evan J.; Cohen, Zsofia P.; Forthman, K. L.; Paulus, Martin P.; Aupperle, Robin L. (Frontiers in Psychology, 2022)
Objective: To further delineate risk and resilience factors contributing to trajectories of mental health symptoms experienced by college students through the pandemic. Participants: n = 183 college students (67.2% female). Methods:. Linear mixed models examined time effects on depression and anxiety. Propensity-matched subgroups exhibiting ‘increased’ versus ‘low and stable’ depression symptoms from before to after the pandemic-onset were compared on pre-pandemic demographic and psychological factors and COVID-related experiences and coping strategies. Results: Students experienced worsening of mental health symptoms throughout the pandemic, particularly during Fall 2020 compared with Fall 2019 (Depression scale d = -0.43 [95% CI: -0.65 to -0.21]). The propensity-matched subgroup exhibiting relative resilience (‘low and stable’ symptoms) reported less alcohol use prior to the pandemic, greater use of active coping strategies, and less of an impact on their college progress. Conclusions: Results point to several potential targets of screening and intervention to decrease residual impacts of the pandemic